PENGGUNAAN SAMBUNGAN BAMBU ORI MENGGUNAKAN BAUT PADA KUDA-KUDA DENGA PENGISI MORTAR RESIN - Muhammad Haris; Lukito Prasetyo (Media Teknik Sipil, 2014)
PENGGUNAAN SAMBUNGAN BAMBU ORI MENGGUNAKANBAUT PADA KUDA-KUDA DENGA PENGISI MORTAR RESINMuhammad Haris 1,Lukito Prasetyo.21&2 Jurusan Teknik Sipil Fakultas Teknik – Universitas Muhammadiyah MalangAlamat korespondensi : Jalan Raya Tlogomas 246 Malang 65144Email : olfurnitur@yahoo.com, prasetyo_lukito@yahoo.comABSTRACTThe use of bamboo as a construction material as well as the price is quite reasonablebecause less tensile strength to accept the burden and the press is quite high, but the use ofbamboo as a construction material has not maxima. This is due to the coupling stalks ofbamboo structure is usually done using conventional ropes, diarrhea and pegs, so thecoupling is less robust. This gives the impression that the power connection is very low, so lookfor an alternative type of connection is stronger, and therefore needed a study for the connectionstructure of bamboo is more solid, the effect of the use of bamboo ori instruction in connectionto the horses bolt with resin mortar filler.From the tests the maximum compressive strength values obtained material resin mortarspecimens at 32 MPa. From the test results on material specimens tap the value of the maximumcompressive robust to be used as filler material in connection ori bamboo horses. Testing theconnection ori bamboo horses given level of loading is: 2000kg, 3000kg, and 4070kg. Bambooeasel Smbungan ori show damage upon receiving load of 4070 kg with a deflection of 8.02mm.Damage to the specimen material is different, this is due to the percentage of the added materialand a different impact. While damage to the connection ori bamboo horses are different, this isdue to the function of each connection is different.Keywords: Bamboo, Resin Mortar, Compressive Strength, Deflection